Garcinia pushpangadaniana (Clusiaceae), a new species from the southern Western Ghats, India - Sabu, Thygarajan; Mohanan, Narayanan Nair; Krishnaraj, Moothedathu Venugopalan Nair; Shareef, Sainudeen Muhammed; Shameer, Peerumuhammed Subaida; Roy, Ponnus Ezabelrajam (Phytotaxa, 2013)
Garcinia pushpangadaniana, a new species of Garcinia from the southern part of the Western Ghats, India, is described, discussed and illustrated. This species is allied to Garcinia xanthochyma.